How lenalidomide is changing the treatment of patients with multiple myeloma - Dimopoulos, M.A.; Terpos, E.; Niesvizky, R. (Critical Reviews in Oncology/Hematology, 2013)
Lenalidomide is a distinct second-generation immunomodulatory drug with multiple anticancer and immunomodulatory effects against hematologic malignancies, in particular multiple myeloma (MM). Dexamethasone synergistically enhances the anticancer effects of lenalidomide, and the combination of lenalidomide and dexamethasone (Len/Dex) is approved for the treatment of patients with relapsed and/or refractory MM. Results from pivotal phase III trials in this setting have demonstrated that Len/Dex extends overall survival compared with dexamethasone alone. Optimal clinical benefits are seen when Len/Dex is initiated at first relapse and continued, beyond best treatment response, until disease progression. Lenalidomide based regimens are also effective as induction therapy in patients with newly diagnosed MM. Importantly, lenalidomide has a predictable and manageable tolerability profile, with minimal neurotoxicity, allowing long-term administration. As the paradigm of myeloma disease continues to change, future studies will determine the efficacy of lenalidomide in novel combinations with potentially complimentary agents. © 2013 Elsevier Ireland Ltd.
Keywords: Dexamethasone; Lenalidomide; multiple myeloma